1976
DOI: 10.1007/bf01464032
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal prediction and outcome at 10/11 years

Abstract: This paper describes some of the findings from the most recent phase of a prospective longitudinal study of firstborns, begun in 1963, to determine the relationship between the primipara's perception of her neonate and the child's subsequent emotional development [1].Previous phases of the study, describing the methodology and discussing the implications of earlier findings, have been reported elsewhere [2, 3, 4] and will not be elaborated. However, some background information is indicated. Method SubjectsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 6 publications
2
16
0
Order By: Relevance
“…Thus, these data are consistent with findings from other studies using different measures and different populations which suggest that negative maternal perceptions of infant behavior may be associated with less than optimal patterns of mothering [8][9][10]. While these studies used primarily questionnaires and rating scales, the current study included independent observations of mother-infant interaction in the home at two points in time.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, these data are consistent with findings from other studies using different measures and different populations which suggest that negative maternal perceptions of infant behavior may be associated with less than optimal patterns of mothering [8][9][10]. While these studies used primarily questionnaires and rating scales, the current study included independent observations of mother-infant interaction in the home at two points in time.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, Bell and Ainsworth [71 have found a negative relationship between infant crying and maternal responsiveness. In a similar vein, Broussard [9,10] has reported that negative maternal perceptions of newborn behavior are associated with a higher incidence of later psychological problems in the offspring. More recently, Milliones [8] reported a correlation between maternal ratings of infant temperament and home visitor's ratings of maternal responsiveness.…”
mentioning
confidence: 89%
“…Similarly, Campbell (1979) also found that the more negative the mother's perception of the infant's temperament, the less responsive she was to his or her crying; Campbell further suggested that lowered maternal responsiveness might have a persistent effect on the quality of caretaking. Broussard (1970Broussard ( , 1976 reported that negative maternal perceptions of infant temperament and behavior were associated with a higher incidence of later psychological problems in the child. The psychological sequelae of poor mother-infant interaction are well documented (Carew-Watts & Chan- Barnett, 1973;ClarkeStewart, 1973;Hess & Shipman, 1965), but whether negative maternal perceptions of the infant's temperament are themselves a problem or whether they serve as a marker for a larger problem is not known.…”
Section: Andrewsmentioning
confidence: 98%
“…Reliability and validity testing of parent assessments have included comparisons between ratings by parents and clinicians on versions of the same measure, comparisons between parent ratings at different time periods, and comparisons between parent ratings and contemporaneous or later developmental measures. Data have been reported for the Neonatal Perception Inventories [10] suggesting that the primipara's perception of her neonate is predictive of her child's subsequent emotional development, for the Denver screening instruments suggesting that parents' ratings are correlated with clinicians' ratings on versions of the same measure [4,5], and for the Infant Temperament Questionnaire suggesting that parents' ratings of temperament are correlated with infant development patterns such as nightwaking [11], walking and talking [12].…”
mentioning
confidence: 95%